SUSTAINABLE DEVELOPMENT STRATEGIES - Ardeleanu, Georgian; Radu, Pietrariu (Economics of Agriculture, 2012)
The concept of sustainable development means the totality of the forms and methods of socio-economic development, whose foundation is primarily to ensure a balance between these socio-economic systems and the natural capital elements. The most common definition of sustainable development is certainly the one given by the World Commission on environment and development (WCED) through the report named "our common Future", also known as the Brundtland Report: "sustainable development is the development that seeks to meet the needs of the present without compromising the ability of future generations to meet their own needs". The following paper seeks to analyse the of various sustainable development strategies, both at European Union level and at the level of Romania.